Multiple Tolerization Reduces Antibody Binding Against Tolerogen Cells: Implications for the Production of Monoclonal Antibodies - De Almeida, Rodrigo [UNESP]; Nakamura, Cecília Naomi [UNESP]; De Lima Fontes, Marina [UNESP]; Da Silva, Julia Paiola [UNESP]; Bertanha, Matheus [UNESP]; Deffune, Elenice [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Moroz, Andrei [UNESP] (SAGE Publications, 2018)
We report an immunization technique that can update the production of monoclonal antibodies (mAbs): the multiple tolerization subtractive immunization (MTSI). A total of 10 BALB/C mice were used. Animals in group 1 received one inoculation of RWPE-1 cells (nontumoral), followed by cyclophosphamide, and then received serial inoculations of nonirradiated PC3 cells (tumoral). Animals in group 2 received our MTSI protocol, as follows: one inoculation of RWPE-1 cells, followed by cyclophosphamide (Cy). This whole tolerization step was repeated three other times, with 14-day intervals between the last Cy exposure and the next RWPE-1 cell inoculation. Finally, the animals received the same nonirradiated PC3 cell exposure as group 1. Blood was taken from each animal, and their polyclonal sera individually tested against the nontumoral RWPE-1 cells in flow cytometry. We found out that, after the MTSI was employed, the serum of the immunized animals, in group 2, contained considerably less antibodies that reacted against the tolerogenic cells, compared with the serum of the animals that underwent regular subtractive immunization. We showed that, by repeating the tolerization cycles, the polyclonal antibodies produced by mice have a reduced specificity toward common/immunodominant epitopes present at nontumoral cells, and thus this technique can be readily used by others in studies involving murine mAb protocols.
Keywords: Hybridoma; Immunization; Monoclonal antibodies; Murine; Subtractive immunization; Tolerization